Annotations on Galatians and Ephesians - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974, 2017)
Volume 58 in the Collected Works of Erasmus series contains, for the first time, the English translation of Erasmus' Annotations on Paul's Epistles to the Galatians and Ephesians.